Pag-aabroad kaunlaran o kapahamakan? - Ballesteros, Soki Paulin; Militante, Clarissa V.; De Dios, Aurora Javate; Hoffman, Cecilia; Santos, Aida; KALAYAAN, Inc. publisher; WEDPRO, Inc. publisher ([Quezon City] [Conspectus, Inc.], 1997)
Precautionary measures against women trafficking in the Philippines.
"Isang proyekto ng CONSPECTUS, Inc., KALAYAAN, Inc., at WEDPRO, Inc. sa ilalim ng Pilot Project Against Trafficking in Women ng mga pamahalaan ng Pilipinas at Belgium sa pamamagitan ng Belgian Administration for Development Cooperation."--Page [3] of cover.
Includes bibliographical references (page 53)
Keywords: Prostitution -- Philippines; Human trafficking -- Philippines; Women foreign workers -- Philippines -- Social conditions; Filipinos -- Employment -- Foreign countries -- Handbooks, manuals, etc; Foreign workers, Filipino -- Handbooks, manuals, etc